The ghostway - Hillerman, Tony (Hillerman, Tony. Leaphorn & Chee novel., 2010)
Old Joseph Joe sees it all. Two strangers spill blood at the Shiprock Wash-O-Mat. One dies. The other drives off into the dry lands of the Big Reservation, but not before he shows the old Navajo a photo of the man he seeks.